2019
DOI: 10.1021/acs.nanolett.8b03685
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Induced Improvements of Perovskite Solar Cell Stability: Effects on Hot-Carriers

Abstract: Hot-carriers, that is, charge carriers with an effective temperature higher than that of the lattice, may contribute to the high power conversion efficiency (PCE) shown by perovskite-based solar cells (PSCs), which are now competitive with silicon solar cells. Hot-carriers lose their excess energy in very short times, typically in a few picoseconds after excitation. For this reason, the carrier dynamics occurring on this time scale are extremely important in determining the participation of hot-carriers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 59 publications
0
63
1
Order By: Relevance
“…40 It has demonstrated that extracting the hot carriers before they totally relax will be the core method for new generation high-efficiency solar cells. 41,42 The hot carrier relaxation is an intraband charge dynamic process, which is inevitably affected by the density of states (DOS) of the valence band (VB) and the conduction band (CB). 21,25,43 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…40 It has demonstrated that extracting the hot carriers before they totally relax will be the core method for new generation high-efficiency solar cells. 41,42 The hot carrier relaxation is an intraband charge dynamic process, which is inevitably affected by the density of states (DOS) of the valence band (VB) and the conduction band (CB). 21,25,43 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCEs are notorious for degrading (via e.g., light-induced degradation [185,186], humidity [187,188], and perovskite-metal reactions due to interdiffusion [189,190]), and even the best PSCs have lifetimes of only thousands of hours [191]. Graphene has been used as a stabilizing agent as, e.g., a protective layer [192][193][194], and transport layer [195][196][197][198][199] and electrode material [200][201][202][203].…”
Section: Applicationsmentioning
confidence: 99%
“…[1][2][3][4] Meanwhile, the exceptional optoelectronic properties of 2D materials and their compatibility with large-scale, solutionprocessable methods (e.g., roll-to-roll printing techniques) lay the ground for the direct integration of low-cost and flexible photovoltaic devices in emerging smart and multifunctional technologies. [5][6][7][8][9][10][11] The beneficial impact of graphene and related 2D materials in PSCs has been demonstrated both in mesoporous [12][13][14][15][16] and inverted planar structures, [17][18][19] as well as in their corresponding tandem systems. 20 Beyond graphene and its derivatives, various 2D material families have been tested including transition metal dichalcogenides, 21 MXenes, 13,22 phosphorene 23,24 and antimonene, 25 just to name a few.…”
Section: Introductionmentioning
confidence: 99%